2021
DOI: 10.3390/metabo11020105
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Trehalose Levels in C. elegans daf-2 Mutants Increase Stress Resistance, Not Lifespan

Abstract: The C. elegans insulin/IGF-1 signaling mutant daf-2 recapitulates the dauer metabolic signature—a shift towards lipid and carbohydrate accumulation—which may be linked to its longevity and stress resistance phenotypes. Trehalose, a disaccharide of glucose, is highly upregulated in daf‑2 mutants and it has been linked to proteome stabilization and protection against heat, cold, desiccation, and hypoxia. Earlier studies suggested that elevated trehalose levels can explain up to 43% of the lifespan extension obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 62 publications
(114 reference statements)
3
20
0
Order By: Relevance
“…The IIS mutant daf-2, bearing a mutation in the insulin/IGF-1 receptor, is characterized by living about twice as long as the wild type and having about five-fold higher trehalose levels compared with the wild type [ 125 ]. Since trehalose function is not only circumscribed as a reserve carbohydrate but also as an important stress-protecting molecule in different organisms, Honda et al analyzed the effect of adding trehalose to the culture medium of C. elegans and found that 5 mM of trehalose extended the lifespan and thermotolerance and retarded aging independently of age state, apparently since trehalose prevents the formation of protein aggregates that normally accumulate with age [ 126 ].…”
Section: Impacts Of Carbohydrate Metabolism On Lifespanmentioning
confidence: 99%
“…The IIS mutant daf-2, bearing a mutation in the insulin/IGF-1 receptor, is characterized by living about twice as long as the wild type and having about five-fold higher trehalose levels compared with the wild type [ 125 ]. Since trehalose function is not only circumscribed as a reserve carbohydrate but also as an important stress-protecting molecule in different organisms, Honda et al analyzed the effect of adding trehalose to the culture medium of C. elegans and found that 5 mM of trehalose extended the lifespan and thermotolerance and retarded aging independently of age state, apparently since trehalose prevents the formation of protein aggregates that normally accumulate with age [ 126 ].…”
Section: Impacts Of Carbohydrate Metabolism On Lifespanmentioning
confidence: 99%
“…In C. elegans , endogenous glucose is stored in the form of trehalose, a non-reducing disaccharide, or glycogen, a branched polysaccharide [ 97 ]. Trehalose presumably acts as a stress protectant against multiple stresses [ 104 , 105 , 106 , 107 , 108 , 109 ] and as a longevity assurance sugar in C. elegans [ 107 , 110 , 111 ]. Although not to the same extent as daf-2 mutants, PHB depletion causes the accumulation of large amounts of trehalose.…”
Section: Phb Has a Broad Impact On The C Elegans Metabolomementioning
confidence: 99%
“…Moreover, trehalose supplementation from the YA stage significantly extends lifespan [ 107 ]. However, the requirement of trehalose for daf-2 longevity has been recently brought into question, because a deficiency in trehalose synthesis mildly shortened daf-2 lifespan [ 109 ], compared with previous studies [ 107 , 111 ]. Similar to trehalose supplementation, exogenous addition of lactate, which induces mitohormesis, leads to stress resistance and survival [ 112 ].…”
Section: Phb Has a Broad Impact On The C Elegans Metabolomementioning
confidence: 99%
“…Other processes occur in dauer larvae to maintain enzyme activity at higher temperatures. For example, in wild-type and daf-2 worms, the presence of exogenous or endogenously produced trehalose increased the thermotolerance of the worms (105,106). Trehalose has also been found to increase the thermal stability of enzymes in vitro (107).…”
Section: Mdh-1 and Mdh-2 Functions In C Elegans Dauer Larvaementioning
confidence: 99%